If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 + x + y = 180 Solving 42 + x + y = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + x + -42 + y = 180 + -42 Reorder the terms: 42 + -42 + x + y = 180 + -42 Combine like terms: 42 + -42 = 0 0 + x + y = 180 + -42 x + y = 180 + -42 Combine like terms: 180 + -42 = 138 x + y = 138 Add '-1y' to each side of the equation. x + y + -1y = 138 + -1y Combine like terms: y + -1y = 0 x + 0 = 138 + -1y x = 138 + -1y Simplifying x = 138 + -1y
| h(-1)=2x^2+4 | | h(0)=2x^2+4 | | 3x+3y=x-2y | | -3z-9z=4/5 | | a^2-2ab+b^2+4a^2b^2=0 | | h(2b)=2x^2+4 | | 18x-24x=1/3 | | 7=-5x+10 | | 4=5d+14 | | 4x+16y=7x+y | | x^2-216= | | 5w+3+w= | | 3/4*3*5 | | an=-2+(n-1) | | y=x^2-5x-9 | | 7x+y=4x+16y | | 5d^2-10d+h=0 | | (y^4/-2z^2)^4 | | X^2+15x+56.25=26.25 | | 5x-5x=200 | | 9=26+3 | | 4-11=17 | | 6f=6f-24 | | g^2-12gh+35h^2=0 | | 5x-25+x+13=180 | | C=4-3X-4Y+2X^2+3Y^2+XY | | logx^2-3logx=-2 | | d^2=490 | | 2b+3(3b+1)=52 | | -3/4x72 | | -4+24=-24 | | d^2-2d+3h=9 |